Chemotherapy combined with radiotherapy can benefit more unresectable HCC patients with portal and/or hepatic vein invasion: a retrospective analysis of the SEER database - Qiu, Xiaotong; Cai, Jianye; Chen, Haitian; Yao, Jia; Xiao, Cuicui; Li, Rong; Xiao, Jiaqi; Zhang, Jiebin; Sui, Xin; Lu, Tongyu; Zheng, Jun; Zhang, Yingcai; et al. (Frontiers in Oncology, 2023)
Background: The purpose of this study is to evaluate the effects of chemotherapy and radiotherapy on the prognosis of unresectable HCC patients with portal and/or hepatic vein invasion. Methods: A retrospective analysis of unresectable HCC patients with portal and/or hepatic vein invasion registered in the Surveillance, Epidemiology, End Results (SEER) database was performed. The propensity score-matching (PSM) method was used to balance differences between groups. Overall survival (OS) and cancer-specific survival (CSS) were the interesting endpoints. OS was calculated from the date of diagnosis to the date of death caused by any cause or the last follow-up. CSS was defined as the interval between the date of diagnosis and date of death due only to HCC or last follow-up. OS and CSS were analyzed by using Kaplan-Meier analysis, Cox proportional hazards model, and Fine-Gray competing-risk model. Results: A total of 2,614 patients were included. 50.2% patients received chemotherapy or radiotherapy and 7.5% patients received both chemotherapy and radiotherapy. Compared to the untreated group, chemotherapy or radiotherapy (COR) (HR = 0.538, 95% CI 0.495-0.585, p < 0.001) and chemotherapy and radiotherapy (CAR) (HR = 0.371, 95% CI 0.316-0.436, p < 0.001) showed better OS. In the COR group, Cox analysis results showed AFP, tumor size, N stage and M stage were independent risk factor of OS. Competing-risk analysis results showed AFP, tumor size and M stage were independent risk factor of CSS. In the CAR group, AFP and M stage were independent risk factors of OS. Competing-risk analysis results showed M stage were independent risk factor of CSS. Kaplan Meier analysis showed chemotherapy combined with radiotherapy significantly improves OS (10.0 vs. 5.0 months, p < 0.001) and CSS (10.0 vs. 6.0 months, p = 0.006) than monotherapy. Conclusion: AFP positive and distant metastasis are the main risk factors affecting OS and CSS of unresectable HCC patients with portal and/or hepatic vein invasion. Chemotherapy combined with radiotherapy significantly improves OS and CSS of unresectable HCC patients with portal and/or hepatic vein invasion.